Peanut Smut in Argentina: An Analysis of the Disease, Advances, and Challenges - Paredes, Juan Andrés; Cazon, Luis Ignacio; Conforto, Erica Cinthia; Rago, Alejandro Mario (American Phytopathological Society, 2024)
Peanut (Arachis hypogaea L.) is a globally high-value food crop, with Argentina ranking third in global peanut exports. However, Argentine peanut production faces a severe threat from a fungal disease, peanut smut, caused by Thecaphora frezzii. This disease is particularly prevalent in the C´ordoba Province, where recent surveys have documented a gradual increase in the prevalence and incidence of peanut smut, becoming a significant challenge to peanut production. First identified in Brazil in the 1960s in wild peanut and later in Argentina in 1995 in commercial peanut fields, the disease has rapidly spread owing to its distinctive pathogen characteristics, including the lack of visible symptoms on aerial plant parts, spore spread, and survival, and with a lack of proactive efforts to develop and apply management strategies.